Laminated solar cell and preparation method thereof

By using a first deposited metal layer to improve adhesion between the metal paste and the cell when preparing the stacked solar cell electrode at low temperature, the problem of high contact resistance in the prior art is solved, and higher conductivity and battery performance are achieved.

CN119546036APending Publication Date: 2025-02-28TRINA SOLAR CO LTD

Patent Information

Application Number
CN202411640576.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the prior art, when preparing laminated solar cell electrodes at low temperatures, the adhesion between the metal paste and the battery is poor, resulting in high contact resistance, affecting electrical conductivity and battery performance.

Method used

In the process of preparing the stacked battery electrode at low temperature, a first deposited metal layer, including 85% to 95% of the metal material (such as silver, gold, copper, aluminum, iron, chromium, dam) is used to improve the adhesion between the metal paste and the battery, and optimize the thickness and structure of the metal layer through multi-layer structure and specific deposition processes (such as electron beam deposition).

Benefits of technology

By increasing the adhesion between the metal paste and the battery, reducing contact resistance, and enhancing the conductivity of the metal electrode, thereby improving the filling factor and overall performance of the stacked solar cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119546036A_ABST
    Figure CN119546036A_ABST
Patent Text Reader

Abstract

The invention provides a laminated solar cell and a preparation method of the laminated solar cell. The laminated solar cell comprises a positive electrode, a first laminated layer, a tunneling composite layer, a second laminated layer and a back electrode, a first deposited metal layer is arranged between the positive electrode and the first laminated layer, and the first deposited metal layer is used for improving the adhesive force between metal slurry and the cell in the process of preparing the electrode of the laminated cell at low temperature. And the contact resistance between the cell and the metal slurry is reduced, so that the conductivity between the metal electrode and the perovskite is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy technology, and in particular to a laminated solar cell and a method for preparing the laminated solar cell. Background Art

[0002] Organic and inorganic metal halide perovskite materials are suitable as the light-absorbing layer of solar cells due to their excellent photoelectric properties and low cost. At the same time, the band gap of perovskite materials is adjustable and can be stacked with other photovoltaic materials with different band gaps to form a stacked solar cell, achieving extremely high photoelectric conversion efficiency. The stacked solar cell of perovskite and crystalline silicon can effectively improve the conversion efficiency of solar cells.

[0003] In the prior art, since the method of preparing electrodes from crystalline silicon at high temperature is directly used in the preparation of tandem cells, the repeatability and stability of the cells will decrease. Therefore, in the preparation of perovskite crystalline silicon tandem solar cells, low-temperature sintering is usually used. However, the printing paste itself contains some polymers. Directly printing metal paste will result in poor adhesion between the paste and the cell, resulting in a large loss in the filling factor of the cell, which seriously affects the contact resistance and conductivity.

[0004] In order to overcome the above-mentioned defects of the prior art, the art is in urgent need of a laminated solar cell technology, which can be used to improve the adhesion between the metal paste and the battery and reduce the contact resistance between the battery and the metal paste during the low-temperature preparation of the laminated battery electrode, thereby improving the conductivity between the metal electrode and the perovskite. Summary of the invention

[0005] A brief summary of one or more aspects is given below to provide a basic understanding of these aspects. This summary is not an exhaustive overview of all conceived aspects, and is neither intended to identify the key or decisive elements of all aspects nor to define the scope of any or all aspects. Its only purpose is to give some concepts of one or more aspects in a simplified form as a prelude to a more detailed description that will be given later.

[0006] In order to overcome the above-mentioned defects of the prior art, the present invention provides a laminated solar cell and a method for preparing a laminated solar cell, which are used to improve the adhesion between the metal slurry and the battery and reduce the contact resistance between the battery and the metal slurry during the low-temperature preparation of the laminated battery electrode, thereby improving the conductivity between the metal electrode and the perovskite.

[0007] Specifically, the stacked solar cell provided according to the first aspect of the present invention comprises a positive electrode, a first stacked layer, a tunneling composite layer, a second stacked layer and a back electrode, wherein a first deposited metal layer is provided between the positive electrode and the first stacked layer.

[0008] Further, in some embodiments of the present invention, the metal material comprises one selected from silver, gold, copper, aluminum, iron, chromium, and molybdenum, or an alloy of two or more metals selected from silver, gold, copper, aluminum, iron, chromium, and molybdenum. Further, in some embodiments of the present invention, the first deposited metal layer comprises 85% to 95% of the metal material by mass.

[0009] Furthermore, in some embodiments of the present invention, the thickness of the first deposited metal layer is 5 nm to 2000 nm.

[0010] Furthermore, in some embodiments of the present invention, the first deposited metal layer includes silver, and the thickness of the first deposited metal layer is 20nm to 2000nm; or the first deposited metal layer includes a metal material selected from gold, copper, aluminum, iron, chromium, molybdenum or silver-copper alloy, and the thickness of the first deposited metal layer is 20nm to 200nm.

[0011] Furthermore, in some embodiments of the present invention, the first deposited metal layer is a multi-layer structure, and the multi-layer structure is formed by depositing multiple layers of the metal material.

[0012] Furthermore, in some embodiments of the present invention, the first deposited metal layer includes a gold-silver double-layer structure or an aluminum-iron double-layer structure.

[0013] Furthermore, in some embodiments of the present invention, the thickness of the gold-silver double-layer structure or the aluminum-iron double-layer structure is 20 nm to 200 nm.

[0014] Furthermore, in some embodiments of the present invention, the thickness of the gold-deposited metal layer in the gold-silver double-layer structure is equal to the thickness of the silver-deposited metal layer, or the thickness of the aluminum-deposited metal layer in the gold-silver double-layer structure is equal to the thickness of the iron-deposited metal layer.

[0015] Furthermore, in some embodiments of the present invention, the deposition process of the first deposited metal layer includes at least one of thermal evaporation deposition, ion beam deposition, reactive plasma deposition, electron beam deposition and sputtering deposition, and the first deposited metal layer is deposited between the positive electrode and the first stack through the deposition process.

[0016] Furthermore, in some embodiments of the present invention, the first deposited metal layer is formed by electron beam deposition, and: the first deposited metal layer uses silver, and its thickness is set to 20nm~2000nm; the first deposited metal layer uses a gold-silver double-layer structure, and its thickness is set to 20nm~200nm; the first deposited metal layer uses a silver-copper alloy, and its thickness is set to 20nm~200nm.

[0017] Further, in some embodiments of the present invention, the first deposited metal layer has a pattern consistent with the metal grid lines between the first stacked layers.

[0018] Furthermore, in some embodiments of the present invention, the stacked solar cell further includes a second deposited metal layer disposed between the back electrode and the second stacked layer.

[0019] Furthermore, in some embodiments of the present invention, the first stack includes a hole transport layer, a first light absorbing layer, an electron transport layer and a first transparent conductive layer, the tunneling composite layer is a transparent conductive oxide layer, and the second stack includes a second transparent conductive layer and a second light absorbing layer.

[0020] In addition, the preparation method of the stacked solar cell provided according to the second aspect of the present invention includes the following steps: preparing the second stack of the stacked solar cell, the second stack having a first surface and a second surface relative to each other, the second surface being a light-receiving surface; forming a tunneling composite layer on the second surface of the second stack; forming a first stack on the surface of the tunneling composite layer away from the second stack; forming a first deposited metal layer on the surface of the first stack away from the tunneling composite layer; and forming a positive electrode on the surface of the first deposited metal layer away from the first stack, and forming a back electrode on the surface of the second stack away from the tunneling composite layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The above features and advantages of the present invention can be better understood after reading the detailed description of the embodiments of the present disclosure in conjunction with the following drawings. In the drawings, the components are not necessarily drawn to scale, and components with similar related properties or features may have the same or similar reference numerals.

[0022] Figure 1 A schematic structural diagram of a stacked solar cell provided according to some embodiments of the present invention is shown.

[0023] Figure 2 A schematic flow chart of a method for preparing a stacked solar cell according to some embodiments of the present invention is shown.

[0024] Figure 3 A material schematic diagram of a tandem solar cell provided according to some embodiments of the present invention is shown.

[0025] Reference numerals:

[0026] 110 Back electrode

[0027] 111 Second stack

[0028] 1111 second transparent conductive layer

[0029] 1112 Second light absorbing layer

[0030] 112 Tunneling composite layer

[0031] 113 First Layer

[0032] 1131 Hole Transport Layer

[0033] 1132 First light absorbing layer

[0034] 1133 Electron Transport Layer

[0035] 1134 first transparent conductive layer

[0036] 114 Positive electrode

[0037] 120 First deposited metal layer

[0038] 121 Second deposited metal layer DETAILED DESCRIPTION

[0039] The following specific embodiments illustrate the implementation of the present invention, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Although the description of the present invention will be introduced in conjunction with the preferred embodiment, this does not mean that the features of this invention are limited to this implementation. On the contrary, the purpose of introducing the invention in conjunction with the implementation is to cover other options or modifications that may be extended based on the claims of the present invention. In order to provide a deep understanding of the present invention, the following description will include many specific details. The present invention can also be implemented without using these details. In addition, in order to avoid confusion or blurring the focus of the present invention, some specific details will be omitted in the description.

[0040] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0041] In addition, the terms "upper", "lower", "left", "right", "top", "bottom", "horizontal" and "vertical" used in the following description should be understood as the directions shown in the paragraph and the related drawings. Such relative terms are only used for the convenience of description and do not mean that the device described therein must be manufactured or operated in a specific direction, and therefore should not be understood as limiting the present invention.

[0042] It is understood that although the terms "first", "second", "third", etc. may be used herein to describe various components, regions, layers and / or parts, these components, regions, layers and / or parts should not be limited by these terms, and these terms are only used to distinguish different components, regions, layers and / or parts. Therefore, the first component, region, layer and / or part discussed below may be referred to as a second component, region, layer and / or part without departing from some embodiments of the present invention.

[0043] As mentioned above, in the prior art, since the method of preparing electrodes from crystalline silicon under high temperature conditions is directly used for the preparation of tandem cells, the repeatability and stability of the cells will decrease. Therefore, in the preparation of perovskite crystalline silicon tandem solar cells, low-temperature sintering is usually used. However, the low-temperature sintering preparation method results in poor conductivity of the metal electrode, thus consuming a large amount of materials used for electrode preparation (e.g., silver paste).

[0044] In order to overcome the above-mentioned defects of the prior art, the present invention provides a laminated solar cell, which is used to improve the adhesion between the metal paste and the battery during the low-temperature preparation of the laminated battery electrode, thereby improving the conductivity of the metal electrode and reducing the amount of metal paste used.

[0045] In some non-limiting embodiments, the method for preparing the tandem solar cell provided in the second aspect of the present invention may be implemented based on the tandem solar cell provided in the first aspect of the present invention.

[0046] Please refer to Figure 1 , Figure 1 A schematic structural diagram of a stacked solar cell provided according to some embodiments of the present invention is shown.

[0047] like Figure 1 As shown, the stacked solar cell includes a positive electrode 114 , a first stack 113 , a tunneling composite layer 112 , a second stack 111 and a back electrode 110 , wherein a first deposited metal layer 120 is disposed between the positive electrode 114 and the first stack 113 .

[0048] In some embodiments, the stacked solar cell further includes a second deposited metal layer 121 disposed between the back electrode 110 and the second stacked layer 111 .

[0049] In some embodiments, the first deposited metal layer 120 includes a metal material, and the metal material includes one selected from silver, gold, copper, aluminum, iron, chromium, and molybdenum, or an alloy of two or more of silver, gold, copper, aluminum, iron, chromium, and molybdenum. Here, the first deposited metal layer should be understood as a single-layer structure, and the metal layer material included in the single-layer structure can be selected from one of the above-mentioned silver, gold, copper, aluminum, iron, chromium, and molybdenum, or an alloy of two or more of silver, gold, copper, aluminum, iron, chromium, and molybdenum.

[0050] In some embodiments, the first deposited metal layer 120 includes 85% to 95% by weight of metal material, and may also include 5% to 15% by weight of epoxy resin and organic additives.

[0051] In some embodiments, the thickness of the first deposited metal layer 120 is 5 nm to 2000 nm.

[0052] In some embodiments, the metal material of the first deposited metal layer 120 may include silver, and the thickness of the first deposited metal layer containing silver may be 20 nm to 2000 nm. Here, since a thickness below 20 nm may result in virtual plating of the metal layer, i.e., discontinuous plating, therefore, selecting a thickness range greater than 20 nm can not only ensure the stability of the plating layer, but also obtain the optimal metal resistivity, thereby improving the overall performance of the solar cell.

[0053] Optionally, the thickness of the silver may be 20 nm to 100 nm. Here, since the resistivity change is usually small above 100 nm, this thickness range can not only ensure the stability of the coating, but also save the amount of metal slurry, thereby reducing the manufacturing cost.

[0054] In some embodiments, the metal material of the first deposited metal layer 120 further includes a metal material selected from gold, copper, aluminum, iron, chromium, molybdenum or silver-copper alloy. Here, the thickness of the first deposited metal layer is 20nm-200nm.

[0055] Here, since the metal layer may be poorly plated if the thickness is less than 20nm, that is, the coating is discontinuous, therefore, selecting a thickness range greater than 20nm can not only ensure the stability of the coating, but also obtain the optimal metal electrode contact resistivity, thereby improving the overall performance of the solar cell. Since the metal electrode contact resistivity changes are usually small above 200nm, therefore, this thickness range can not only ensure the stability of the coating, but also save the amount of metal slurry, thereby reducing manufacturing costs.

[0056] Here, since conventional gold, silver and copper have relatively good conductivity, the change in metal electrode contact resistivity with increasing thickness after 20nm is relatively small. However, since aluminum, iron, chromium and molybdenum have poorer conductivity, compared with gold, silver and copper, when the thickness is increased by the same amount, the change in metal resistivity is relatively large, and the conductivity is improved more.

[0057] In some embodiments, the second stack 111 of the stacked solar cell includes a second transparent conductive layer 1111 and a second light absorbing layer 1112. Here, the second transparent conductive layer 1111 is generally a transparent conductive oxide film (e.g., ITO, IZO, IWO), which can be used to allow light to penetrate and serve as an anode at the same time. The second light absorbing layer 1112 may include at least one of crystalline silicon, perovskite, CdTe, CIGS and GaAs materials. Here, the second light absorbing layer 1112 may also use a heterojunction cell (Heterojunction with Intrinsic Thin-Layer, HJT), thereby reducing the preparation process and improving the preparation efficiency.

[0058] In some embodiments, the tunneling recombination layer 112 of the stacked solar cell may use at least one of ITO, IWO and Ag to help electrons pass through the material levels faster and reduce the recombination loss of electrons within the material, thereby improving the electron transmission efficiency and overall performance of the battery.

[0059] In some embodiments, the first stacked layer 113 of the stacked solar cell includes a hole transport layer 1131 , a first light absorption layer 1132 , an electron transport layer 1133 and a first transparent conductive layer 1134 .

[0060] In some embodiments, in the first stack 113 of the solar cell, the hole transport layer 1131 may include a self-assembled monolayer and an anchoring layer. Specifically, the anchoring layer includes ITO, IZO, IWO, FTO, ICO, AZO, BZO, nanocrystalline silicon, TiO2, SnO2, NiO x and AlO x The self-assembled monolayer in the hole transport layer 1131 includes at least one of [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz), [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz), benzoic acid, and 4-[bis(2,4-dimethoxybiphenyl-4-yl)amino]-biphenyl-4-carboxylic acid (MC-43).

[0061] Those skilled in the art will understand that the structure of the hole transport layer 1131 is only a non-limiting embodiment provided by the present invention, which is intended to clearly demonstrate the main concept of the present invention and provide a specific solution that is easy for the public to implement, rather than to limit the scope of protection of the present invention.

[0062] Optionally, in some other embodiments, in the first stack 113 of the solar cell, the hole transport layer 1131 may also include multiple p-type layers for transporting holes, wherein the p-type layer material includes at least one of p-type single crystal silicon, p-type polycrystalline silicon, p-type amorphous silicon and single-molecule self-assembly material, and its thickness is not more than 100 μm.

[0063] In some embodiments, the first light absorption layer 1132 may be made of a perovskite material for absorbing photons and generating electron-hole pairs. The perovskite material is a three-dimensional structure ABX3, where A is a monovalent cation, B is a divalent cation, and X is a monovalent anion, wherein the monovalent cation A includes but is not limited to a mixture of one or more monovalent cations of cesium (Cs), rubidium (Rb), methylamine (CH3NH3), and guanidine (CH2NH2)2, the divalent cation B includes but is not limited to a mixture of one or more divalent cations of lead (Pb), copper (Cu), zinc (Zn), gallium (Ga), tin (Sn), and calcium (Ca), and the monovalent anion X includes but is not limited to a mixture of one or more monovalent anions of iodine (I), bromine (Br), chlorine (Cl), fluorine (F), and thiocyanate ion (SCN). Here, the perovskite material can be coated on a self-assembled monolayer via at least one of a doctor blade coating method, a slit coating method, a screen printing method, and an inkjet printing method, and the thickness thereof can be 10 nm to 100 μm, and the band gap thereof can be 0.9 eV to 3.0 eV. Before preparation, the perovskite precursor is usually mixed with a plurality of solvents to obtain a perovskite precursor solution, wherein the molar ratio of the various solvents to the precursor complex is (0.001 to 1).

[0064] In some embodiments, the electron transport layer 1133 may further include: a plurality of n-type layers for transporting electrons, wherein the n-type layer material includes n-type single crystal silicon, n-type polycrystalline silicon, n-type amorphous silicon, TiO2, SnO2, ZnO, ZrO2, GZO, IZO, FTO, ITO, BaSnO3, TiSnO x SnZnO x , fullerene and its derivatives, and its thickness is not more than 100 μm.

[0065] In some embodiments, the first transparent conductive layer 1134 is generally a transparent conductive oxide film (eg, ITO, IZO, IWO), which can be used to allow light to pass through and serve as a cathode.

[0066] In some embodiments, the material of the metal paste of the positive electrode 114 and / or the back electrode 110 includes at least one of Au, Ag, Al, Cu, graphene, TCO and nanocrystalline silicon, and the thickness thereof may be no greater than 10 μm.

[0067] In some embodiments, the first deposited metal layer 120 can be deposited before printing the metal paste to improve the adhesion between the metal paste and the battery during the low-temperature preparation of the laminated battery electrode, thereby improving the conductivity of the metal electrode and reducing the amount of metal paste used.

[0068] In some embodiments, the deposition process of the first deposited metal layer 120 includes at least one of thermal evaporation deposition, ion beam deposition, reactive plasma deposition, electron beam deposition, and sputtering deposition, and the first deposited metal layer 120 is deposited between the positive electrode 114 and the first stacked layer 113 via the deposition process. The first deposited metal layer 120 may have a pattern consistent with the metal grid lines between the first stacked layers 113.

[0069] Furthermore, the vacuum pressure of the thermal evaporation deposition process is 4×10 -4 torr, voltage is 3V, current is 160A, evaporation rate is The vacuum pressure of the reactive plasma deposition process is 3×10 -5 torr, the current is 130A, the electron gun argon gas flow rate is 40sccm, the chamber protection gas is argon, and the evaporation rate is The vacuum pressure of electron beam deposition process is 4×10 -4 torr, voltage is 20kV, single gun power is 70W~100W, evaporation rate is

[0070] Further, in some embodiments, the first deposited metal layer 120 can be formed by electron beam deposition, and: the first deposited metal layer 120 can be made of silver with a thickness of 20nm to 2000nm; the first deposited metal layer 120 can be made of a gold-silver double-layer structure with a thickness of 20nm to 200nm; the first deposited metal layer 120 can be made of silver-copper alloy with a thickness of 20nm to 200nm.

[0071] In some embodiments, the first deposited metal layer 120 is a multilayer structure, and the multilayer structure is formed by depositing multiple layers of metal materials. The metal layer material contained in the multilayer structure can be selected from one of the above-mentioned silver, gold, copper, aluminum, iron, chromium, and molybdenum, or an alloy of two or more metals among silver, gold, copper, aluminum, iron, chromium, and molybdenum. Preferably, the first deposited metal layer 120 may include a gold-silver double-layer structure or an aluminum-iron double-layer structure. The thickness of the gold-silver double-layer structure or the aluminum-iron double-layer structure is 20nm to 200nm. The thickness of the gold-deposited metal layer in the gold-silver double-layer structure is equal to the thickness of the silver-deposited metal layer, or the thickness of the aluminum-deposited metal layer in the gold-silver double-layer structure is equal to the thickness of the iron-deposited metal layer.

[0072] Here, the metal layer of the multi-layer structure can reduce the resistance of the first deposited metal layer 120. Specifically, the metal layer of the multi-layer structure can reduce the contact resistance with the metal electrode while depositing a more stable metal to achieve the purpose of improving stability.

[0073] The working principle of the above-mentioned tandem solar cell will be described below in conjunction with some embodiments of the preparation method of the tandem solar cell. Those skilled in the art will understand that these embodiments of the tandem solar cell method are only some non-limiting implementation methods provided by the present invention, and are intended to clearly demonstrate the main concept of the present invention and provide some specific solutions that are convenient for the public to implement, rather than to limit the entire preparation method of the tandem solar cell.

[0074] Please refer to Figure 2-3 , Figure 2 A schematic flow chart of a method for preparing a stacked solar cell according to some embodiments of the present invention is shown. Figure 3 A material schematic diagram of a tandem solar cell provided according to some embodiments of the present invention is shown.

[0075] like Figure 2-3 As shown, the method for preparing the stacked solar cell may first perform step S1: preparing the second stacked layer 111 of the stacked solar cell, wherein the second stacked layer 111 has a first surface and a second surface opposite to each other, and the second surface is a light-receiving surface.

[0076] Specifically, the preparation method of the second light absorbing layer 1112 first selects an N-type silicon wafer; on the second surface of the N-type silicon wafer, an intrinsic amorphous silicon layer and an N-type amorphous silicon layer are sequentially prepared, wherein the N-type amorphous silicon layer is the second surface of the second light absorbing layer 1112; and on the first surface of the N-type silicon wafer, an intrinsic amorphous silicon layer and a P-type amorphous silicon layer are sequentially prepared, wherein the P-type amorphous silicon layer is the first surface of the second light absorbing layer 1112. For example: the maximum height h of the surface line marks of the N-type silicon wafer can be 5μm, and the maximum inclination angle θ of the surface line marks of the N-type silicon substrate is 30°. Then, a PECVD method is used to sequentially prepare an intrinsic amorphous silicon layer with a thickness of 5nm and an N-type amorphous silicon layer with a thickness of 20nm on the second surface of the N-type silicon wafer. After that, a PECVD method is used to sequentially prepare an intrinsic amorphous silicon layer with a thickness of 5nm and a P-type amorphous silicon layer with a thickness of 20nm on the first surface of the N-type silicon wafer. Then, a second transparent conductive layer 1111 is formed on the first surface of the second light absorbing layer 1112. For example, a transparent conductive oxide layer ITO is formed on the surface of the P-type amorphous silicon layer away from the N-type silicon wafer by sputtering, with a thickness of 130 nm.

[0077] Afterwards, the method for preparing the stacked solar cell may first perform step S2 : forming a tunneling composite layer 112 on the second surface of the second stack 111 .

[0078] Specifically, the tunneling composite layer 112 can be prepared on the second surface of the second light absorbing layer 1112 by sputtering a transparent conductive oxide layer ITO with a thickness of 50 nm on the surface of the N-type amorphous silicon layer away from the N-type silicon wafer.

[0079] Thereafter, the method for preparing the stacked solar cell may perform step S3 : forming a first stacked layer 113 on a surface of the tunneling composite layer 112 away from the second stacked layer 111 .

[0080] Specifically, a NiO layer with a thickness of 30 nm is prepared on the surface of the second surface tunneling composite layer 112 (transparent conductive oxide layer) ITO by magnetron sputtering. Then, a perovskite light absorbing layer Cs0.25FA0.75Pb(I0.8Br0.2)3 is formed on the surface of the NiO layer by solution spin coating, with a band gap of approximately 1.68ev and a thickness of 500nm. After that, a C60 layer with a thickness of 15 nm is prepared on the surface of the perovskite light absorbing layer by thermal evaporation, and a SnO2 layer with a thickness of 15 nm is prepared on the surface of the C60 layer by atomic layer deposition. After that, an ITO layer with a thickness of 100 nm is prepared on the surface of the SnO2 layer by sputtering.

[0081] Optionally, before preparing the C60 layer on the surface of the perovskite light-absorbing layer, a LiF layer with a thickness of 2 nm can be prepared to prevent oxidation or corrosion of the electrode surface to reduce the loss in the energy conversion process inside the solar cell, thereby improving the stability and life of the solar cell.

[0082] Thereafter, the method for preparing the stacked solar cell may perform step S4 : forming a first deposited metal layer 120 on a surface of the first stacked layer 113 away from the tunneling composite layer 112 .

[0083] Finally, the method for preparing a stacked solar cell may execute step S5: forming a positive electrode 114 on a surface of the first deposited metal layer 120 away from the first stack 113 , and forming a back electrode 110 on a surface of the second stack 111 away from the tunneling composite layer 112 .

[0084] Optionally, before forming the back electrode 110 on the surface of the second stack 111 away from the tunneling composite layer 112, a second deposited metal layer 121 may be prepared. Here, the physical and chemical characteristics of the second deposited metal layer are the same as those of the first metal layer, which will not be described again.

[0085] Please refer to Table 1, which shows an embodiment and a comparative example of the performance parameters of the stacked battery based on the structure that the stacked battery has the first deposited metal layer 120.

[0086]

[0087] As shown in Table 1, in the comparative example, the stacked battery does not have the first deposited metal layer 120, so the contact resistivity between the metal electrode and the battery is the largest (60Ω·cm). Specifically, when the metal paste in the metal electrode is sintered at a low temperature, the resin and other organic substances are not sintered completely, resulting in poor contact between the metal electrode and the battery.

[0088] Furthermore, since the printing paste of the metal electrode contains a small amount of non-conductive organic matter, directly printing the metal electrode will result in a higher contact resistance between the electrode and the battery. After the metal layer is deposited, the contact resistance between the deposited metal layer and the battery decreases, and no contact resistance is generated between the large amount of metal particles in the printed electrode paste and the deposited metal layer. Therefore, the overall contact resistance decreases, which directly leads to a sharp increase in the filling factor in the battery performance, thereby greatly improving the conversion efficiency of the device.

[0089] In summary, the laminated solar cell provided by the present invention can be used to improve the adhesion between the metal electrode and the battery during the low-temperature preparation of the laminated battery electrode, thereby improving the conductivity of the metal electrode and improving the fill factor of the laminated battery.

[0090] Although the above methods are illustrated and described as a series of actions for simplicity of explanation, it should be understood and appreciated that these methods are not limited by the order of the actions, because according to one or more embodiments, some actions may occur in a different order and / or concurrently with other actions from those illustrated and described herein or not illustrated and described herein but understandable to those skilled in the art.

[0091] The previous description of the disclosure is provided to enable any person skilled in the art to make or use the disclosure. Various modifications to the disclosure will be apparent to those skilled in the art, and the general principles defined herein may be applied to other variations without departing from the spirit or scope of the disclosure. Thus, the disclosure is not intended to be limited to the examples and designs described herein, but should be granted the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A stacked solar cell, characterized in that: The stacked solar cell comprises a positive electrode, a first stacked layer, a tunneling composite layer, a second stacked layer and a back electrode, wherein a first deposited metal layer is provided between the positive electrode and the first stacked layer.

2. The tandem solar cell according to claim 1, characterized in that: The first deposited metal layer includes a metal material, wherein the metal material includes one selected from silver, gold, copper, aluminum, iron, chromium, molybdenum Or an alloy of two or more metals selected from silver, gold, copper, aluminum, iron, chromium and molybdenum.

3. The stacked solar cell according to claim 2, characterized in that: The first deposited metal layer includes 85% to 95% by mass of the metal material.

4. The tandem solar cell according to claim 2, wherein: The thickness of the first deposited metal layer is 5 nm to 2000 nm.

5. The stacked solar cell according to claim 4, characterized in that: The first deposited metal layer includes silver, and the thickness of the first deposited metal layer is 20nm~2000nm; or the first deposited metal layer includes a metal material selected from gold, copper, aluminum, iron, chromium, molybdenum or silver-copper alloy, and the thickness of the first deposited metal layer is 20nm~200nm.

6. The tandem solar cell according to claim 2, characterized in that: The first deposited metal layer is a multi-layer structure, and the multi-layer structure is formed by depositing multiple layers of the metal material.

7. The tandem solar cell according to claim 6, characterized in that: The first deposited metal layer includes a gold-silver double-layer structure or an aluminum-iron double-layer structure.

8. The tandem solar cell according to claim 7, characterized in that: The thickness of the gold-silver double-layer structure or the aluminum-iron double-layer structure is 20nm-200nm.

9. The tandem solar cell according to claim 8, characterized in that: The thickness of the gold deposited metal layer in the gold-silver double-layer structure is equal to the thickness of the silver deposited metal layer, or the thickness of the aluminum deposited metal layer in the gold-silver double-layer structure is equal to the thickness of the iron deposited metal layer.

10. The tandem solar cell according to any one of claims 1 to 9, characterized in that: The deposition process of the first deposited metal layer includes at least one of thermal evaporation deposition, ion beam deposition, reactive plasma deposition, electron beam deposition and sputtering deposition, and the first deposited metal layer is deposited between the positive electrode and the first stack through the deposition process.

11. The tandem solar cell according to claim 1, characterized in that: The first deposited metal layer is formed by electron beam deposition, and: The first deposited metal layer is made of silver, and its thickness is set to 20nm to 2000nm; The first deposited metal layer adopts a gold-silver double-layer structure, and its thickness is set to 20nm-200nm; The first deposited metal layer is made of silver-copper alloy, and its thickness is set to 20nm-200nm.

12. The tandem solar cell according to claim 1, characterized in that: The first deposited metal layer has a pattern consistent with the metal grid lines between the first stacked layers.

13. The tandem solar cell according to claim 1, characterized in that: The invention also includes a second deposited metal layer, which is arranged between the back electrode and the second stacked layer.

14. The tandem solar cell according to claim 1, characterized in that: The first stack includes a hole transport layer, a first light absorption layer, an electron transport layer and a first transparent conductive layer, the tunnel composite layer is a transparent conductive oxide layer, and the second stack includes a second transparent conductive layer and a second light absorption layer.

15. A method for preparing the stacked solar cell according to any one of claims 1 to 14, characterized in that: The following steps are involved: Prepare a second stack of the stacked solar cell, wherein the second stack has a first surface and a second surface opposite to each other, and the second surface is a light-receiving surface; forming a tunneling composite layer on the second surface of the second stack; forming a first stacked layer on a surface of the tunneling composite layer away from the second stacked layer; forming a first deposited metal layer on a surface of the first stack away from the tunneling composite layer; as well as A positive electrode is formed on a surface of the first deposited metal layer away from the first stack, and a back electrode is formed on a surface of the second stack away from the tunneling composite layer.

Citation Information

Patent Citations

  • Composite back electrode, preparation method thereof and laminated solar cell

    CN111384187A

  • Laminated perovskite solar cell and manufacturing method thereof

    CN114447025A

  • Solar cell, manufacturing method thereof and photovoltaic module

    CN116981270A

  • Preparation method of heterojunction solar cell

    CN118263360A

  • Solar cell based on micro-nano structure

    CN213546329U

Cited By

  • Tandem solar cell and preparation method

    WO2026103185A1